FENOMENA PENYEBARAN PANDEMI COVID 19 DAN KESENJANGAN GENDER DI ASIA TENGGARA (STUDI KASUS: DAMPAK COVID 19 TERHADAP PEMENUHAN HAK ASASI PEREMPUAN DI INDONESIA (2020-2021) - Nala Nourma Nastiti; I Wayan Aditya Harikesa (Universitas Jenderal Ahmad Yani, 2023)
The COVID-19 pandemic has left so much impact all over the world. The social impact caused by the SARS-CoV-2 virus is also very significant in Asia. It is women who are disproportionately affected. For example, in several countries in Southeast Asia and the Pacific, girls are less fortunate because they are seen as an economic burden. Likewise in Indonesia as one of the countries in Southeast Asia, where many cases of gender inequality occur. The method used in writing this research is descriptive qualitative analysis with data collection through documentation, observation and interviews. This research will focus on the impact of the COVID 19 pandemic on the fulfillment of women's human rights in Indonesia during 2020-2021 as a case study of the phenomenon and spread of the COVID 19 pandemic and the gender gap in SoSutheast Asia. The research will produce data on gender relations in the midst of the COVID-19 pandemic, especially in Southeast Asia and Indonesia as one of the countries with the highest population and influence in Southeast Asia.